PEMAHAMAN MAHASISWA DALAM PENGGUNAAN GOOGLE CLASSROOM PADA PEMBELAJARAN DARING - Muhammad Azzarkasyi; Dian Aswita; Syamsul Rizal (JURNAL SERAMBI ILMU, 2022)
This study aims to determine students' understanding of using Google Classroom as anonline learning medium at FKIP USM. The method used in this study is descriptiveanalysis with a quantitative approach and data analysis using percentages. The subjectsin this study were students of the natural sciences (Physics, Mathematics, Biology, andChemistry) environment FKIP Universitas Serambi Mekkah, amounting to 51 people.The instrument used in this study was a student understanding questionnaire. Based onthe results of this study, there are 1 respondent (2%) who responds very high, 5respondents (10%) responds high, 35 respondents (69%) responds moderately, 9respondents (18%) responds low, and 1 respondent (2%) ) responds very low. Based onthe results of research on student understanding in the use of Google Classroom inonline learning, it can be concluded that it is good, this is evident from student datamaking it easier to store and access documents such as material or importantassignments sent via Google Classroom, so that if students have not had time to printthe required documents, they can access them first through Google Classroom. Inaddition, students are also facilitated to obtain announcements given by lecturersquickly (real time) so that they become effective and efficient in terms of time.